Diagnóstico da semeadura mecanizada de soja na fronteira oeste do Rio Grande do Sul - (:unkn) unknown (Universidade Federal do Pampa, 2018)
One of the elements that contribute to the success in the establishment of the soybean crop is the uniformity of seed distribution in the sowing groove. This factor ensures the ideal population of plants and consequently the productivity of the crop. In this context, the objective of this study was to diagnose the quality of mechanized sowing of soybean in rural properties in the West Frontier of the state of Rio Grande do Sul. To this end, the spaces between plants in production, culture, soy, and In addition, questionnaires were made to the producer, with the actions related to the sowing process. Sampling was carried out in 50 soybean crops, which were collected in four plant subsamples, totaling 160 plants fore ach tractor/ seed set. From the analysis of the data i tis possible to observe a great use of the no-tillage system and the precision, pneumatic and alveolated discotheque mechanisms, most selected for the crop. With regard to the importance, it is visible the underutilization of tractors, with seeders that exposein manytimes, half the power offered bythe tractor. From a parallel between the densityof asowing and apopulation of plants reached, areduction of more than 50% in some properties can be estimated. Speed did not interfere with acceptable, double and faulty spaces. In the calculation of the coefficient of variation, it is possible to perceive the high dispersion of the analyzed data, that is, the spacings between plants varied significantly in the sowing line.
Diagnosis of soybean sowingmechanized onthe westborder of Rio Grande do Sul
Keywords: Engenharia agrícola; Glycine max L; Semeadura; Agricultural engineering; Seeding; CNPQ::CIENCIAS AGRARIAS